Involvement of glucose-regulated protein 78 and spliced X-box binding protein 1 in the protective effect of gliclazide in diabetic nephropathy. (December 2018) - Zhang, Ying-Wen; Wang, Xiuping; Ren, Xiaodan; Zhang, Manling
Highlights: Endoplasmic reticulum stress contributes to the development of diabetic nephropathy. The Grp78 and sXbp1 mRNA and protein levels increased in diabetic nephropathy rats. Gliclazide treatment lessens the kidney injury in diabetic nephropathy rats. Gliclazide treatment lower the Grp78 and sXbp1 mRNA and protein levels. Gliclazide alleviates diabetic nephropathy probably by suppressing the ER responses. Abstract: Aims: To testing whether endoplasmic reticulum (ER) stress contributes to the development of diabetic nephropathy. Investigated the effect of gliclazide, an oral antihyperglycemic agent, in a rat model of diabetic nephropathy and the underlying mechanism related to the ER stress response. Methods: Sixty SD rats were divided into six groups. Diabetic nephropathy was induced in 30 rats with a streptozotocin (STZ) injection and high fat diet, which were then treated with saline, gliclazide or 4-PBA. 20 rats were treated with Tunicamycin (TM) one-time intraperitoneal injection, following treated with saline or gliclazide. Blood glucose, kidney index and function were evaluated. Light and transmission electron microscopy (TEM) were used to observe kidney histological changes. Quantitative real-time PCR and western blot were performed to access the mRNA and protein levels of glucose-regulated protein 78 (GRP78) and spliced X-box binding protein 1 (sXBP1) in glomeruli. Result: STZ-induced diabetic rats evidenced nephropathy by higher serum creatinine (sCr), blood urea nitrogen (BUN), microalbuminuria (MAU), and kidney index. Histological examination and TEM assay showed abnormal renal structures including thick glomerular basement membrane and mesangial cell expansion. The same changes were found in TM-treated rats. Gliclazide-treated had similar kidney index, but lower glucose levels, sCr, BUN, and MAU, compared with both saline and 4-PBA-treated diabetic rats or saline-treated TM rats. Synchronize with significantly lower Grp78 and sXbp1 mRNA and protein levels. Conclusion: Diabetes-induced nephropathy is associated with ER stress. Gliclazide treatment lessens diabetic nephropathy, probably partially by suppressing the GRP78- and sXBP1-mediated ER response.